LANGUAGE RIGHTS IN POSTCOLONIAL AFRICAN LITERATURES: A MARXIST PERSPECTIVE - DJOSSOU AGBOADANNON, Koumagnon Alfred; BONOU GBO, Zakiath (My University, 2023)
The political decolonization of Africa in the period of independence has soon bumped on a crucial obstacle on the way: the question of the language in postcolonial African literatures. In this regard, several well-known writers and essayists such as Ngũgĩ, Fanon, and Kunene have offered their approach to this question and expressed their full support for the production of texts in African languages as the way to mind liberation. The promotion of mother tongues is proposed by Ngũgĩ in his book Decolonizing the Mind: the Politics of Language in African Literature (1986) to analyze and sustain the paradigm change. However, the question remains delicate given to the fact that the multilingual meaning of literatures expressed in a foreign language in Africa constitutes a diversity and a strength assumed by other writers. The question of the language in postcolonial African literatures is answered here with a Marxist perspective to reveal and preserve the quality, the influence and the international reputation of the African authentic creation.
Keywords: African language; African literature; postcolonial; education; nationalism; Marxism